Commentarius in Dannielem Prophetam, Lamentationes et Baruch - Knabenbauer, Iosepho (Summptibus P. Lethielleux, Editoris, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage